Activation of CRH receptor type 1 expressed on glutamatergic neurons increases excitability of CA1 pyramidal neurons by the modulation of voltage-gated ion channels - Kratzer, Stephan; Mattusch, Corinna; Noll-Hussong, Michael; Eder, Matthias; Kafitz, Karl W.; Metzger, Michael W.; Dedic, Nina; Deussing, Jan M.; Holsboer, Florian; Kochs, Eberhard; Rammes, Gerhard (Frontiers in Cellular Neuroscience, 2013)
Corticotropin-releasing hormone (CRH) plays an important role in a substantial number of patients with stress-related mental disorders, such as anxiety disorders and depression. CRH has been shown to increase neuronal excitability in the hippocampus, but the underlying mechanisms are poorly understood. The effects of CRH on neuronal excitability were investigated in acute hippocampal brain slices. Population spikes (PS) and field excitatory postsynaptic potentials (fEPSP) were evoked by stimulating Schaffer-collaterals and recorded simultaneously from the somatic and dendritic region of CA1 pyramidal neurons. CRH was found to increase PS amplitudes (mean ± Standard error of the mean; 231.8 ± 31.2% of control; n = 10) while neither affecting fEPSPs (104.3 ± 4.2%; n = 10) nor long-term potentiation (LTP). However, when Schaffer-collaterals were excited via action potentials (APs) generated by stimulation of CA3 pyramidal neurons, CRH increased fEPSP amplitudes (119.8 ± 3.6%; n = 8) and the magnitude of LTP in the CA1 region. Experiments in slices from transgenic mice revealed that the effect on PS amplitude is mediated exclusively by CRH receptor 1 (CRHR1) expressed on glutamatergic neurons. The effects of CRH on PS were dependent on phosphatase-2B, L- and T-type calcium channels and voltage-gated potassium channels but independent on intracellular Ca2+-elevation. In patch-clamp experiments, CRH increased the frequency and decay times of APs and decreased currents through A-type and delayed-rectifier potassium channels. These results suggest that CRH does not affect synaptic transmission per se, but modulates voltage-gated ion currents important for the generation of APs and hence elevates by this route overall neuronal activity.